PARTICULARIDADES ANESTÉSICAS EM TAMANDUÁ-MIRIM (TAMANDUA TETRADACTYLA): RELATO DE CASO - DA SILVA, TAIZA; Moreira Silva, Ana Clara; Ferreira de Oliveira, Nayara Cristina; Rodrigues Barbosa Ferreira, Ana Flávia; da Silva Gonçalves, Larissa; Barboza Alves, Karoline; Antunes de Lima, Marcos Paulo (Sinapse Múltipla, 2023)
Não se aplica